2013
DOI: 10.1089/jayao.2012.0038
|View full text |Cite
|
Sign up to set email alerts
|

Coping Styles of Female Adolescent Cancer Patients with Potential Fertility Loss

Abstract: Purpose: The purpose of this qualitative study was to assess the coping styles of female adolescent cancer patients regarding potential loss of fertility. Expectations and desires for the future, coping styles in typical adolescence, and coping styles when faced with potential loss of fertility due to cancer treatment are discussed. Methods: Female adolescents diagnosed with cancer aged 12-18 years at study (N = 14) were administered a 10-item values clarification tool to pilot test the readability and relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 36 publications
1
55
1
Order By: Relevance
“…It is also important to note the support that adolescents and parents gave for having these conversations, even in the absence of options. The importance of early and frequent conversations is supported by other studies that have looked at the lack of congruence between adolescents and parents, the coping styles of adolescent females, and gender disparities in fertility related services(59, 60). …”
Section: Discussionmentioning
confidence: 91%
“…It is also important to note the support that adolescents and parents gave for having these conversations, even in the absence of options. The importance of early and frequent conversations is supported by other studies that have looked at the lack of congruence between adolescents and parents, the coping styles of adolescent females, and gender disparities in fertility related services(59, 60). …”
Section: Discussionmentioning
confidence: 91%
“…Fertility preservation is one of the most under-prescribed and least implemented services, 27 and studies have found that providers do not have adequate knowledge, referral sources, or comfort discussing sexuality with adolescents and young adults in their 20s. 28,29 The impact that cancer treatment has on fertility capacity derives from patient factors (e.g., genetic endowment, gender, age at treatment, current Throughout the treatment phase, AYAs should also receive regular counseling about pregnancy prevention and sexually transmitted disease risk reduction.…”
Section: Developmentalmentioning
confidence: 99%
“…Unfortunately, oncology clinicians often underestimate the relevance of psychosexual issues among AYAs and do not discuss SRH . Although AYAs consistently identify the need for greater patient‐clinician SRH communication, these conversations rarely take place . This study aims to explore AYA perceptions and experiences of SRH communication in the oncology setting and to identify barriers and facilitators to guide the development of effective communication strategies and practice guidelines.…”
Section: Introductionmentioning
confidence: 99%